(untitled) (Revista de Ciências Agroveterinárias, 2021)
Drought stress is one of the main limiting factors of crop production. For this reason, plants have developed mechanisms of survival and acclimatization to the drought condition, for instance, the stomatal closure to minimize the loss of water by the plant. In effect, the plant’s responses to water deficit are directly controlled by the hormonal balance. Thus, the present study aimed to evaluate how different tomato hormonal mutants respond to drought stress. Five tomato genotypes were used, the cultivar Micro-Tom (MT), wild-type, the mutants Never ripe (Nr), with low sensitivity to ethylene, diageotropica (dgt), with low sensitivity to auxin, and the transgenic L19 (with high biosynthesis of gibberellin) and SL (with low biosynthesis of strigolactones). Plants were grown in polyethylene pots with 350 mL filled with commercial substrate. During development, all plants were irrigated daily until the beginning of the drought stress, 37 days after sowing (DAS). Then, irrigation was suspended in part of the plants for seven days to induce drought. Control plants were irrigated continuously. After seven days in the respective conditions (irrigated and drought stress), the plants were harvested to analyze the growth, relative water content (RWC), and electrolyte leakage. As expected, L19 plants exhibited higher height, while SL plants showed greater fresh and dry shoot weight accumulation in control conditions. In drought stress conditions, a reduction in fresh weight and plant height was observed in all evaluated genotypes. In contrast, only MT and SL plants did not suffer a reduction in dry mass of the aerial part due to water restriction. As for the CRA, only L19 plants did not show a reduction under water deficit conditions.